On a comparison method for pulse systems in the space $R^n$ - Akhmetov, M. U.; Perestyuk, N. A. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
A method for the study of differential equations with pulse influence on the surfaces, which was realized in [1] for a bounded domain in the phase space, is now extended to the entire space $R^n$. We prove theorems on the existence of integral surfaces in the critical case and justify the reduction principle for these equations.